ACQUISITION OF INFORMATION RESOURCES IN UNIVERSITY LIBRARIES IN SOUTH-EAST: PROSPECTS AND CHALLENGES (NAU Journal of Library and Information Science, 2022)
The purpose of this study was to determine the prospects and challenges to the acquisition of information resources in university libraries in South East Nigeria. Two research questions guided the study. A descriptive survey research design was adopted. The population of this study comprised all the 157 catalogue librarians in the cataloguing section in the 10 public university libraries in the South-East Nigeria. No sampling was done as the population was of manageable size. The two sets of questionnaires titled ‘Prospects of the Acquisition of Library Resources in University Libraries Questionnaire (PALRULQ)’ and Challenges to the Acquisition of Library Resources in University Libraries Questionnaire (CALRULQ)’ were used for data collection. The questionnaires were structured on four- point rating scale. Data collected were analysed using mean score rating. Item with 2.5 mean rating and above was regarded as positive. The findings of the study revealed that increase in the variety of books for use by library patrons; increase in the currency of information resources; availability of information resources for teaching by lecturers; availability of information resources for learning by students, availability of information resources for research  as well as the provision of opportunity to weed out less vital information resources were the prospects of acquisition of library resources.Furthermore, the findings revealed that  inadequate funding; lack of required materials locally; over protection of government’s documents; poor resource allocation; poor resource utilization; lack of clearly defined acquisition policy; out-sourcing; change in publication date and adherence to due process were challenges militating against acquisition practices. Based on the findings, it was recommended that acquisition librarians should ensure that only resources that meet the needs and preference of its patrons are purchased and that such acquisitions should be guided by a well-articulated collection development policy.
Keywords: Acquisition; Information Resources; Librarians; University Libraries; Acquisition Policy; Southeast Nigeria